Association Between Duration of Antiretroviral Therapy and Virological Suppression Among HIV Patients in South Sulawesi, Indonesia - Cut Indriputri; M. Askar (Direktorat Politeknik Kesehatan Makassar, 2025)
HIV infection remains a major global health problem requiring lifelong therapy to suppress viral replication. Antiretroviral therapy (ART) has been proven effective in reducing viral load; however, its success may vary depending on treatment duration and patient adherence. This study aimed to analyze the relationship between ART duration and virological status among HIV patients receiving first-line ART in South Sulawesi, Indonesia. This descriptive cross-sectional study used medical record data from patients who underwent viral load testing at the referral laboratory in South Sulawesi. A total of 221 patients who had received ART for at least six months were included. The main variables were ART duration (in months) and virological status, categorized as successful (≤1000 copies/mL) or failed (>1000 copies/mL). Data were analyzed descriptively using frequency and percentage distributions. Most patients in all treatment duration groups achieved virological suppression, with success rates ranging from 90% to 100%. Virological failure was observed in 3.6% of patients, particularly in those with treatment durations of 144–166 months. Overall, 96.4% of patients achieved successful virological suppression, meeting the national target, This study demonstrates high rates of virological suppression among HIV patients in South Sulawesi, supporting the effectiveness of first-line ART programs in the region. Routine viral load monitoring and continuous adherence support are essential to sustain long-term treatment success. Future research should include immunological and adherence parameters to provide a more comprehensive evaluation of treatment outcomes.